Biophysical characterization of oligomerization and fibrillization of the G131V pathogenic mutant of human prion protein. (18th November 2019) - Zhang, Meilan; Zhang, Haoran; Yao, Hongwei; Guo, Chenyun; Lin, Donghai
Abstract: The pathogenesis of fatal neurodegenerative prion diseases is closely associated with the conversion of α-helix-rich cellular prion protein into β-sheet-rich scrapie form. Pathogenic point mutations of prion proteins usually promote the conformational conversion and trigger inherited prion diseases. The G131V mutation of human prion protein (HuPrP) was identified to be involved in Gerstmann–Sträussler–Scheinker syndrome. Few studies have been carried out to address the pathogenesis of the G131V mutant. Here, we addressed the effects of the G131V mutation on oligomerization and fibrillization of the full-length HuPrP(23–231) and truncated HuPrP(91–231) proteins. The G131V mutation promotes the oligomerization but alleviates the fibrillization of HuPrP, implying that the oligomerization might play a crucial role in the pathogenic mechanisms of the G131V mutant. Moreover, the flexible N-terminal fragment in either the wild-type or the G131V mutant HuPrP increases the oligomerization tendencies but decreases the fibrillization tendencies. Furthermore, this mutation significantly alters the tertiary structure of human PrP C and might distinctly change the conformational conversion tendency. Interestingly, both guanidine hydrochloride denaturation and thermal denaturation experiments showed that the G131V mutation does not significantly change the thermodynamic stabilities of the HuPrP proteins. This work may be of benefit to a mechanistic understanding of the conformational conversion of prion proteins and also provide clues for the prevention and treatment of prion diseases.